Desenvolvimento de um interpretador de expressões de teoria dos conjuntos para fins didáticos - Reis, Fellipe de Souza (2023)
The teaching of engineering in the field of Computational Mathematics is fundamental for the training of the graduate and encompasses various subjects, such as discrete mathematics, logic, among others. However, there is a scarcity of software to aid in the learning of students in higher education computer science courses, which motivates the implementation of such tools. In both the field of computer science and mathematics, set theory proves to be vital in establishing the foundations of both disciplines, and knowledge of this theory is a basic requirement for understanding the Computer Theory. Among the various types of software that can assist in learning are interpreters, which can be used both for assisting in the resolution of practice exercises and creating examples for comprehension. Interpreters are programs that execute instructions written in a specific language. This work addressed the construction and design of a complete interpreter for set theory expressions for didactic purposes with an interactive interface. The basic literature of compilers, in conjunction with the Python language, was used for this purpose. As a final result of the work, a complete interpreter with lexical, syntactic, and semantic analyzers was constructed. Performance and correctness experiments presented demonstrate its effectiveness and efficiency.